PENCIPTAAN BUDAYA HIDUP BERSIH PERSPEKTIF ISLAM MASA PANDEMI COVID-19? DI PONDOK MODERN GONTOR PUTRI 1 MANTINGAN - Nur Indah Fitriana; Cerly Dwi Qarlina (Intelegensia : Jurnal Pendidikan Islam, 2021)
AbstractThe Covid-19 pandemic has had a major impact in Indonesia. In addition to the health sector which has been affected by Covid-19, the education sector has also experienced a major impact. Educational institutions throughout Indonesia are experiencing major changes in their teaching and learning processes, which have shifted to online learning. However, this cannot be done by educational institutions with a boarding school system because all learning activities are carried out by gathering and huddling. Therefore, the implementation of health protocols and a healthy life culture is carried out in the Islamic boarding school environment. The purpose of this research is to describe and explain the clean or healthy culture implemented by Pondok Modern Gontor Putri 1 as an effort to prevent the transmission and spread of the covid-19 virus. This study uses a qualitative descriptive method with a case study approach. The results showed that in order to protect the residents in the Pondok Modern Gontor Putri environment, health protocols and a culture of clean or healthy living must be carried out together. It is easy to implement health protocols and tighten hygiene culture because of the disciplined character education that has always been enforced at Pondok Modern Gontor Putri 1 since its inception.  Keywords: Creation of  a clean living culture; Islamic perspective; Covid-19; Islamic boarding school